Spectrophotometric method for the determination of amlodipine besylate in pure and dosage forms using 7,7,8,8-tetracyanoquinodimethane and tetracyanoethylene - Nina Alizadeh; Fatimeh Hemati (Faculty of Pharmacy, Cairo University, 2014)
Two simple, rapid and sensitive spectrophotometric methods for the determination of amlodipine besylate (ADB) in pure form and in pharmaceutical preparations have been developed. The methods are based on the charge transfer reactions between the drug as electron donor with 7,7,8,8-tetracyanoquinodimethane (TCNQ) and tetracyanoethylene (TCNE) as π-acceptors in order to the formation of charge transfer (CT) complexes. These reactions give colored products which have maximum absorption bands at 745 and 396 nm for TCNQ and TCNE, respectively. Beer's law is obeyed in the concentration ranges 20-110 μg mL−1 and 5-35 μg mL−1 for ADB using TCNQ and TCNE reagents. The molar absorptivities are 2.73 × 103 and 6.43 × 103 L mol−1 cm and the Sandell (S) sensitivities are 0.14 μg cm−2 and 0.063 μg cm−2 using TCNQ and TCNE reagents, respectively, which indicate the high sensitivity of the proposed methods. The relative standard deviations (R.S.D.: 0.94 and 0.73) obtained using TCNQ and TCNE reagents, respectively, refer to the high accuracy and precision of the proposed method.